1999
DOI: 10.1007/pl00005375
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterisation of 5-HT receptors positively coupled to adenylyl cyclase in the rat hippocampus

Abstract: The pharmacological properties of 5-hydroxytryptamine (5-HT) receptors positively coupled to adenylyl cyclase in the rat hippocampus were investigated using selective agonists and antagonists. 5-HT (0.008-125 microM) stimulated cyclic AMP formation in homogenates of rat hippocampus in a concentration-dependent manner. The maximal increase in cyclic AMP formation occurred at 1 microM (141+/-6%) and the half-maximal effect (EC50) at 50+/-22 nM. Cyclic AMP accumulation induced by 1 microM 5-HT was partly inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…In Waeber and Moskowitz's (1995) study the masking of 5-HT 1A binding sites by 100 nM 8-OH-DPAT is likely to block a large fraction of the 5-HT 7 receptor binding sites because of the affinity of this compound for the 5-HT 7 receptor Plassat et al, 1993;Ruat et al, 1993;Shen et al, 1993). In Gustafson et al (1996), the concentration of pindolol (160 nM (Markstein et al, 1999;Thomas et al, 1999) demonstrated an interaction of 5-HT 1A and 5-HT 7 receptors in hippocampus. The 5-HT 7 receptor-mediated stimulation of adenylyl cyclase activity by 5-CT seems to be augmented by a mechanism involving 5-HT 1A receptor activation.…”
Section: Discussionmentioning
confidence: 95%
“…In Waeber and Moskowitz's (1995) study the masking of 5-HT 1A binding sites by 100 nM 8-OH-DPAT is likely to block a large fraction of the 5-HT 7 receptor binding sites because of the affinity of this compound for the 5-HT 7 receptor Plassat et al, 1993;Ruat et al, 1993;Shen et al, 1993). In Gustafson et al (1996), the concentration of pindolol (160 nM (Markstein et al, 1999;Thomas et al, 1999) demonstrated an interaction of 5-HT 1A and 5-HT 7 receptors in hippocampus. The 5-HT 7 receptor-mediated stimulation of adenylyl cyclase activity by 5-CT seems to be augmented by a mechanism involving 5-HT 1A receptor activation.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, functional studies in rat jaw-closing spinal motor neurons have coupled activation of the metabotrophic 5-HT 1A receptor to down-regulation of the apamin-sensitive I mAHP (45). The exact pathway mediating this effect in spinal motor neurons is unknown, but activation of the 5-HT 1A receptor induces downstream cAMP accumulation and PKA activation (46). Therefore, activation of 5-HT 1A receptors in spinal motor neurons may result in direct phosphorylation of the SK2 subunit and modulation of the I mAHP .…”
Section: Discussionmentioning
confidence: 99%
“…In Aplysia, activation of mitogen-activated protein kinases by serotonin is implicated in memory formation and occurs through a G scoupled 5-HT receptor (32,33). In mammalian brain, 5-HT 4 and 5-HT 7 receptors are both found in the hippocampus (36,37), and 5-HT 7 receptors were recently shown to activate ERKs in cultured hippocampal neurons (35). The importance of ERK activation for the involvement of these receptors in learning and memory (38) remains to be determined.…”
Section: Activation Of Erk1/2 Through 5-ht 4(b) and 5-ht 7(a) Receptomentioning
confidence: 99%
“…In cultured rat hippocampal neurons, 5-HT activated ERK1/2 through 5-HT 7 receptors, but the mechanism was not characterized (35). In mammalian brain, both 5-HT 4 and 5-HT 7 receptors are found in the hippocampus (36,37), and these receptors are both believed to be important in learning and memory (38). Thus, there is a need to determine whether 5-HT 4 and 5-HT 7 receptors can activate ERK, as well as the mechanism for such activation.…”
mentioning
confidence: 99%